The effect of giving moringa leaf extract (Moringa oleifera) in feed on the level of cannibalism and growth of Asian seabass Lates calcarifer (Bloch, 1790) - Nurlianti Nurlianti; Asni Anwar; Hamsah Hamsah; Akmaluddin Akmaluddin; Farhanah Wahyu; Murni Murni; Walda Dewi Berliana; Eva Ayuzar (Universitas Malikussaleh, 2026)
Asian seabass (Lates calcarifer) is a high-value aquaculture species, but cannibalism during the juvenile stage remains a major constraint. This study aimed to evaluate the effect of moringa (Moringa oleifera) leaf extract supplementation in feed on cannibalism rate, growth performance, and survival of Asian seabass juveniles. A completely randomized design (CRD) was applied with four treatments and three replications: control (A) and moringa extract at concentrations of 1:10 (B), 1:15 (C), and 1:20 g/mL (D). The results showed that moringa leaf extract supplementation had no significant effect (p > 0.05) on cannibalism rate and survival. However, a trend of reduced cannibalism and improved growth performance was observed, particularly in treatment B (1:10 g/mL), which produced the highest growth. In conclusion, moringa leaf extract shows potential as a functional feed additive, although further studies with improved experimental design and additional parameters are required to confirm its effectiveness. Keywords: Cannibalism; Feed; Lates calcarifer; Moringa olifera